A trimeric glycosylated GH45 cellulase from the red abalone (Haliotis rufescens) exhibits endo and exoactivity. - L Joshua Hernández-Benítez; Miguel A Ramírez-Rodríguez; Alejandra Hernández-Santoyo; Adela Rodríguez-Romero (PLoS ONE, 2024)
The red abalone (Haliotis rufescens) represents North America's most important aquaculture species. Its hepatopancreas is rich in cellulases and other polysaccharide-degrading enzymes, which provide it the remarkable ability to digest cellulose-rich macroalgae; nevertheless, its cellulolytic systems are poorly explored. This manuscript describes some functional and structural properties of an endogenous trimeric glycosylated endoglucanase from H. rufescens. The purified enzyme showed a molecular mass of 23.4 kDa determined by MALDI-TOF mass spectrometry, which behaved as a homotrimer in gel filtration chromatography and zymograms. According to the periodic acid-Schiff reagent staining, detecting sugar moieties in SDS-PAGE gel confirmed that abalone cellulase is a glycoprotein. Hydrolysis of cello-oligosaccharides and p-nitrophenyl-β-D-glucopyranosides confirmed its endo/exoactivity. A maximum enzyme activity toward 0.5% (w/v) carboxymethylcellulose of 53.9 ± 1.0 U/mg was achieved at 45°C and pH 6.0. We elucidated the abalone cellulase primary structure using proteases and mass spectrometry methods. Based on these results and using a bioinformatic approach, we identified the gene encoding this enzyme and deduced its full-length amino acid sequence; the mature protein comprised 177 residues with a calculated molecular mass of 19.1 kDa and, according to sequence similarity, it was classified into the glycosyl-hydrolase family 45 subfamily B. An AlphaFold theoretical model and docking simulations with cellopentaose confirmed that abalone cellulase is a β-sheet rich protein, as also observed by circular dichroism experiments, with conserved catalytic residues: Asp26, Asn109, and Asp134. Interestingly, the AlphaFold-Multimer analysis indicated a trimeric assembly for abalone cellulase, which supported our experimental findings. The discovery and characterization of these enzymes may contribute to developing efficient cellulose bioconversion processes for biofuels and sustainable bioproducts.